Femoro-jugular cannulation in veno-venous extracorporeal membrane oxygenation PRO/CON - Crivellari, Martina (J Thorac Dis, 2018)
Veno-venous (VV) extracorporeal membrane oxygenation (ECMO) is the most efficient technique for respiratory support. It is based on a patient adequate circulation and cardiac function and it is indicated for isolated lung failure after optimization of the ventilatory support and the medical treatment. We describe PRO and CONs of the Femoro-jugular (F>J) approach, as an ideal setting for patients which require high flow (>5 L/min), such as those with extreme hypoxemia and/or septic shock. This technique can be accomplished very quickly at the bedside also in an unstable patient.